PEMBAGIAN HARTA WARISAN PADA MASYARAKAT ETNIS JAWA KECAMATAN BILAH BARAT KABUPATEN LABUHAN BATU DALAM PERSPEKTIF HUKUM ISLAM - Hafsah, Syauqon Hilali Nur Ritonga Ansari Yamamah (AT-TAFAHUM: Journal of Islamic Law, 2018)
The dividing of inheritance on javanese civil of sub-regency bilah barat the regency of labuhan batu on islamic law study that the dividing of inheritance is dividing inheritance based on system sagendhong sapikul and sighar semangka and divided the inheritance based five pillar of system,Â  those are; a) Angayani, b) Angomahi, c) Angayomi, d) Angayemi and e) Angamatjani. And the Islamic law see it that the dividing inheritance no fitting to Islamâs verse on Quran and hadis both based on mawaris study or farÃ¡idh study. It means the certain of dividing inheritance on Javanese ethnic of sub-regency Bilah Barat based on justice system, meanwhile on Quran shows the boy has gotten two more then womanâs right. And the effect approaches to three fights those are the murder, fomenter, and stamping on close.